Depolymerization of Cellulose and Synthesis of Hexitols from Cellulose Using Heterogeneous Catalysts. Issue 3 (10th June 2014) - Rout, Prasant Kumar; Nannaware, Ashween Deepak; Prakash, Om; Rajasekharan, Ram
Abstract Sustainable, economic, and industrial growth of any nation is based on an integrative approach in utilizing renewable biomass feedstock. Lignocellulosic biomass has come up as the most important candidate for the production of different valuable biochemicals and biofuels. Cellulose isolated from lignocellulosic biomass is exploited for the production of glucose and high‐value hexitols. Innovative catalyst design holds the key to fundamental advances in the transformation of cellulose to high‐value sugars and biochemicals. In this review paper, several heterogeneous catalytic approaches for depolymerization of cellulose and synthesis of hexitols from cellulose have been summarized. In addition, HMF (5‐hydroxymethylfurfural) and LA (levulinic acid) are important biochemicals derived from cellulose. The industrial importance of biochemicals derived from HMF and LA are also highlighted in this article. Therefore, this review is an attempt to provide a brief glimpse of the lignocellulosic biomass refinery‐related efforts, which are currently taking place around the world.